TECHNOLOGICAL INNOVATIONS IN EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The aim of this study is to investigate the attitudes of students at Westminster International University in Tashkent (WIUT) towards the use of Artificial Intelligence for different academic purposes. The research helps to analyze students’ perceptions on AI in different areas, such as assistance for learning and self-improving, career development, helper in the assessment tasks and others, as the usage of AI becoming popular day by day in academia. Online questionnaire method, which is created on Google platform, was used to collect data on students’ perspectives and involvements with AI. The respondents were asked to fulfill the questionnaire, which contains various kinds of question types, such as multiple choice, open-ended, Likertscale.  The findings demonstrates that all students in the Certificate of International Foundation Studies (CIFS) have experienced AI for different aims from getting feedback for their written work, to cheating through using AI generated tools to paraphrase or complete the work for themselves. Results showed that a huge number of students using AI to finish their academic tasks to get a good mark, while some of them considered it as plagiarism and not reliable. Overall, CIFS students have knowledge to implement Artificial Intelligence in Academia.